Harmony and The Role of Actors to Actualize of Social Resilience in Purworejo and Tabanan - Saleh, Rahmat; Oktafiani, Irin; Aruan, Norman Luther; Iban, Angela (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2021)
Rukun and Tri Hita Karana had been conceptualized by scholars in anthropology as harmony in the Javanese and Balinese people from the late 20th until the early 21st century. These two kinds of philosophies still relevant amid the significant changes in the so-called modern society of Javanese and Balinese. This paper shows how rukun and Tri Hita Karana, which have been renowned along time will ensure the social resilience in the people of Purworejo and Tabanan when they are facing challenges. These two regions also remain still by the supports of organic actors who are ready to secure the harmony in the society. Data in this paper is collected from the focus group discussion and in-depth interviews in Purworejo and Tabanan as part of the research Penelitian Pembentukan Desa Berketahanan Sosial which is conducted in 2019 by Social Welfare Research and Development Agency of The Ministry of Social Services of Indonesia. Furthermore, this paper analyzed the meaning of harmony in the Purworejo and Tabanan people and their ability to face any changes. The results are; (1) Rukun and Tri Hita Karana still relevant in the people of Purworejo and Tabanan; (2) there are some organic actors who then help the society to keep the long-live philosophy of rukun and Tri Hita Karana.